Phenolic Acids Released in Maize Rhizosphere During Maize-Soybean Intercropping Inhibit Phytophthora Blight of Soybean - Zhang, He; Yang, Yuxin; Mei, Xinyue; Li, Ying; Wu, Jiaqing; Li, Yiwen; Wang, Huiling; Huang, Huichuan; Yang, Min; He, Xiahong; Zhu, Shusheng; Liu, Yixiang (Frontiers in Plant Science, 2020)
Interspecies interactions play a key role in soil-borne disease suppression in intercropping systems. However, there are limited data on the underlying mechanisms of soil-borne Phytophthora disease suppression. Here, a field experiment confirmed the effects of maize and soybean intercropping on soil-borne disease caused by Phytophthora sojae. Experimentally, it was found that roots and root exudates of maize could attract the zoospores of P. sojae and inhibit the motility of zoospores and germination of cystospores. Furthermore, five phenolic acids (p-coumaric acid, cinnamic acid, p-hydroxybenzoic acid, vanillic acid, ferulic acid) consistently identified in the root exudates and rhizosphere soil of maize were found to interfere with the infection behaviour of P. sojae. Among them, cinnamic acid showed significant chemotaxis to zoospores, and p-coumaric acid and cinnamic acid showed strong antimicrobial activity against P. sojae. In the rhizosphere soil of soybean, however, only p-hydroxybenzoic acid, low concentrations of vanillic acid, and ferulic acid were identified. Importantly, the coexistence of five phenolic acids in the maize rhizosphere, compared with three phenolic acids in the soybean rhizosphere, showed strong synergistic antimicrobial activity against the infection behaviour of P. sojae. In summary, the type and concentrations of phenolic acids in maize and soybean rhizosphere soils was the crucial factor in Phytophthora disease suppression in this intercropping system.